2020
DOI: 10.1002/jms.4669
|View full text |Cite
|
Sign up to set email alerts
|

A critical comparison of three MS‐based approaches for quantitative proteomics analysis

Abstract: MS‐based proteomics is expanding its role as a routine tool for biological discovery. Nevertheless, the task of accurately and precisely quantifying thousands of analytes in a single experiment remains challenging. In this study, the diagnostic accuracy of three popular data‐dependent methods for protein relative quantification (label‐free [LF], dimethyl labelling [DML] and tandem mass tags [TMT]) has been assessed using a mixed species proteome (three species) and five experimental replicates per condition. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Specificity, sensitivity, and precision values measured in this study after MQ-L analysis were globally in line with previously published results, presented in comparison with those obtained using labeling methods . Furthermore, a recent study showed that MQ-L outperformed other quantitative tools (not including PD) according to several statistical metrics, highlighting the value of the results achieved by the approaches compared in this study.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Specificity, sensitivity, and precision values measured in this study after MQ-L analysis were globally in line with previously published results, presented in comparison with those obtained using labeling methods . Furthermore, a recent study showed that MQ-L outperformed other quantitative tools (not including PD) according to several statistical metrics, highlighting the value of the results achieved by the approaches compared in this study.…”
Section: Resultssupporting
confidence: 91%
“…A lower CV could be observed in normalization-based methods also when considering background proteins. The CV values measured here for MQ-L quantification were consistent to those reported by other groups in standard protein mixture and cell line experiments.…”
Section: Resultssupporting
confidence: 90%
“…Isobaric labeling with tandem mass tags (TMT) is a popular multiplexing strategy for mass spectrometry-based proteomics. It labels peptides from different samples with isobaric variants of a mass tag, combines them into a single biological mixture, and profiles the mixture in a single mass spectrometry run. , This strategy allows us to both gain the accuracy of relative protein quantification and increase the sample throughput. , However, since TMT experiments are limited to up to 18 samples in a single mixture, larger-scale cohorts require multiple TMT mixtures. Increasingly, TMT-based investigations combine repeated measures designs and the use of multiple TMT mixtures. For example, recent studies from the CPTAC consortium compared protein abundances between tumor and adjacent normal tissues in a paired design with more than 100 patients and 20 mixtures. As another example, Nie et al used a hybrid design to investigate the changes in protein abundances among different organs after SARS-CoV-2 virus infection with 93 patients and 22 mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…label-based proteomic approaches (e.g., SILAC) are expensive and time consuming ( Taverna and Gaspari, 2021 )…”
Section: Introductionmentioning
confidence: 99%